Zusanli (ST36) Acupoint Injection With Dexamethasone for Chemotherapy-Induced Myelosuppression: A Systematic Review and Meta-Analysis - Chen, Jiangfeng; Lin, Zhixian; Ding, Jiyuan (Frontiers in Oncology, 2021)
Objective Myelosuppression is the most common adverse reaction of chemotherapy, which seriously affects the course of treatment. Zusanli (ST36) acupoint injection with dexamethasone has achieved good clinical efficacy in China. This study aimed to systematically evaluate the efficacy of ST36 acupoint injection with dexamethasone in the treatment of chemotherapy-induced myelosuppression (CIM). Methods Randomized controlled trials of CIM treated with ST36 acupoint injection with dexamethasone were retrieved from eight electronic databases. We used the Cochrane Collaboration tool to assess the risk of bias. Excel 2010 was used to establish a database for information extraction, and RevMan 5.3.0 software was used to analyze the included test data. GRADE profiler 3.6 software was used to grade the quality of evidence for the outcome indicators of the study. Results A total of 17 studies involving 1177 patients were included in this meta-analysis. The results showed that, compared with conventional western medicine (CWM), ST36 acupoint injection with dexamethasone could significantly improve the clinical total effective rate [RR=1.95, 95% CI (1.53, 2.49), P <0.00001] and increase white blood cell (WBC) (MD=1.38, 95% CI (0.74, 2.01), P<0.0001) and hemoglobin (Hb) levels [MD=3.89, 95% CI (1.57, 6.20), P=0.001]. In addition, ST36 acupoint injection with dexamethasone can shorten recovery time of myelosuppression [MD=-3.94, 95% CI (-4.97 to -2.91), P<0.00001] and improve Karnofsky performance status [MD=10.7, 95% CI (1.36, 20.05), P=0.02<0.05]. However, there was no significant difference among ST36 acupoint injection with dexamethasone and CWM in platelet (PLT) elevation [MD=4.61, 95% CI (-10.14, 19.35), P=0.54]. Conclusion This study found that ST36 acupoint injection with dexamethasone had a positive effect on CIM. However, more studies with well-designed, large sample size, strict randomization, and clear descriptions about detection and reporting processes are needed in the future to further confirm the efficacy of ST36 acupoint injection with dexamethasone in the treatment of CIM. Systematic Review Registration https://www.crd.york.ac.uk/, identifier CRD42021223979.